Diversity and conservation of the Gredos Regional Park peatlands (Iberian Central System, Spain): Geomorphological and geobotanical characterisation and incoming threats - López Sáez, José Antonio; Lautenschlaeger, Reyes Luelmo; Carrasco, Rosa M.; Pedraza, Javier; Sánchez-Mata, Daniel; Luengo-Nicolau, Enrique (Mediterranean Botany, 2023)
High-mountain peatlands are essential ecosystems for habitats, biodiversity, water, and carbon cycling, but there is little comprehensive information in central Iberia. We present results of research concerning the distribution, geormorphology, floristic, geobotany, and habitat diversity of peatlands in the Gredos Regional Park (Iberian Central System). We identified 72 peatlands covering 117 ha and ranging in size from 0.01 to 17.34 ha. Peatlands occur primarily in the upper orosubmediterranean bioclimatic belt at 1775–2230 m asl. From a geomorphological point of view, 9 different peatland typologies have been defined. Multivariate analyses (agglomerative cluster analysis and principal component analysis) of 103 relevés allowed us to classify the sampled peatland stands into 7 plant communities and 4 European habitats that formed along complex hydrogeomorphic conditions, and to propose a new subassociation of other community previously described (Caricetum echinato-nigrae lycopodielletosum inundatae). The main threat to Gredensean peatlands is pastoral pressure, which affects 15 of them intensively, mainly between the upper supramediterranean and the lower orosubmediterranean bioclimatic belts (~1314–1700 m asl). Seven bryophytes and three vascular plants documented in the Gredos Regional Park peatlands are included in the IUCN Red List. From the point of view of conservation priority, the most threatened correspond to transition mires communities (Habitat 7140) growing in oligotrophic and minerotrophic peatlands (Caricion nigrae vegetation). Particularly, the Iberian Central System endemic Sedo lagascae-Eriophoretum latifolii association is the one that has achieved the highest score in the five criteria considered in this regard because Meesia triquetra, a species with the category of “critically endangered”, inhabits it.